HARMONI MASYARAKAT ISLAM DAN HINDU DI DESA LINGSAR, KABUPATEN LOMBOK BARAT (Ditinjau dari Perspektif Pierre Bourdieu) - Kholidi, Ahmad Khaerul (LP2M IAIN Palopo, 2018)
This paper provides us with an understanding of Bourdieu's theory. How the tolerance between Muslims and Hinduism comes as a religion that upholds the values of tolerance. The Islam and Hinduism communities of Lingsar are able to fortify and form harmony and even become a direction for religions outside the village of Lingsar that still form a harmony between both communities of Islam and Hindu. In Lingsar village there are two different Islam and Hindu religious communities but in their daily life they are able to create a peaceful and harmonious life. Thus Lingsar Village should be used as a village that maintains tolerance in religious attitude. The study looked at Bourdeiu's viewpoint of habitus, ranging from the concept of harmony to society, the advent of Islam and Hinduism in Lombok, and the harmonious relation between Islam and Hinduism in the ritual frame and festival of the show.